Normal physiology. Methodical manual for students - Kushch, O. G.; Sukhomlinova, I. Ye.; Tikhonovskay, M. A.; Tikhonovskiy, A. V.; Chugin, S. V.; Yeryomina, A. K.; Kirsanova, E. V.; Кущ, Оксана Георгіївна; Сухомлінова, Ірина Євгенівна; Тихоновська, Марина Анатоліївна; Тихоновський, Олександр Володимирович; Чугін, Сергій Вячеславович; et al. (Zaporizhzhia state medical university, 2017)
This manual is recommended for II year students of International Faculty of specialty "General medicine" studying normal physiology, to prepare for practical class module 1, module 1 and licensing exam "KROK 1: General medical".
Практикум по нормальній фізіології